2014
DOI: 10.1007/s00284-014-0645-1
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation by Chlorella vulgaris is Affected by Light Quality

Abstract: Formation of biofilm on surfaces is a common feature in aquatic environments. Major groups of inhabitants in conditions where light is present are photoautotrophic microorganisms, such as cyanobacteria and microalgae. This study examined the effect of light quality on growth and biofilm formation of the microalgal species Chlorella vulgaris. Dense biofilm formation and aggregated growth of cells were observed in treatments exposed to blue, purple and white light. Less dense biofilm formation and solitary growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…In contrast, those grown under low irradiance using the same inoculum were thinner, more compact and included a wider variety of species, including cyanobacteria. Hultberg et al (2014) demonstrated the direct effect of light quality using monochromatic illumination in biofilm formation; indicating that light quality can improve cellular growth and lipid content at the same time. Furthermore, the authors concluded that the optimal wavelength depends on the species and showed the potential for using light as a tool for managing algal biofilm formation and harvesting.…”
Section: Light Intensitymentioning
confidence: 94%
“…In contrast, those grown under low irradiance using the same inoculum were thinner, more compact and included a wider variety of species, including cyanobacteria. Hultberg et al (2014) demonstrated the direct effect of light quality using monochromatic illumination in biofilm formation; indicating that light quality can improve cellular growth and lipid content at the same time. Furthermore, the authors concluded that the optimal wavelength depends on the species and showed the potential for using light as a tool for managing algal biofilm formation and harvesting.…”
Section: Light Intensitymentioning
confidence: 94%
“…accumulated the greatest lipid amount under blue light as this specific light wavelength stimulated the enzymatic activities of carbonic anhydrase and ribulose bi-phosphate carboxylase/ oxygenase to form triglycerides, but protein content extracted from microalgae under four different lights remained similar. It was also discovered that white, blue and purple lights were able to give higher biofilm formation of Chlorella vulgaris than red, yellow and green lights alone [ 87 ].…”
Section: Factors Affecting Production Of Extracellular Polymeric Substancesmentioning
confidence: 99%
“…adhesion was tested on nine different materials and microalgal biofilm formation was optimal on a glass-fiber-reinforced plastic with concave structure [16]. As opposed to materials such as glass or natural or synthetic fibers, membranes can be considered as an ideal substrate for biofilms formation due to their large surface area and tunable surface properties, such as pore size and porosity [11,17,18]. Another advantage of using membranes is that pores in the membrane can be used to supply water, mineral nutrients and/or CO 2 [19].…”
Section: Accepted Manuscriptmentioning
confidence: 99%